TAK MENDENGAR TAPI MELIHAT - Fadhila Saktia; Desfiarni Desfiarni; Indra Yuda (SENDRATASIK UNP, 2013)
Abstract This article explained about the dance title ‘’ Not Hear but see ‘’ as anew creation telling a about group of people born as normal creatures and the other born with hearing impairment. The existence of those msde the one with lacks had low self-esteem, and feit sad. This dance was a kind of dramatic dances which was presented symbolically. It is also considered as conteporer dance. The problem potrayed in the dance was that human being was not a perfect creature, in which each of them had their own strengths and weaknesses. The ending of this explained that the deaf people and the common ones could have a mutual understanding and lived together by dismissing the social gaps between them and be grateful for the life they had. Keywords : Tak, mendengar, tapi, melihat